CHAOS THEORY AS DEPICTED IN THE ADJUSTMENT BUREAU - Laliyah Khairun Novia; Nurenzia Yannuar (Celt: A Journal of Culture, English Language Teaching & Literature, 2015)
The Adjustment Bureau movie is an example of how Chaos Theory, a theory originated from Physics, can be applied in a work of popular cultural product. This paper analyzes how Chaos Theory's Butterfly Effect, in which one small event brings significant effects, presents in events affecting David Norris' future life. The paper firstly discloses the main character's (David Norris) life as Determined by the Bureau. It then focuses on how slight mistakes change the supposed outcome of his life. Lastly, chaos leads to the compatibilist idea proposing the reconciliation or Determinism and Tree Will.